2012
DOI: 10.1007/s00360-012-0727-y
|View full text |Cite
|
Sign up to set email alerts
|

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered

Abstract: We investigated the ability of domestic cats to regulate the macronutrient composition of their diet when provided with foods that differed not only in macronutrient content but also in texture and moisture content, as typically found in the main forms of commercially manufactured cat foods. Cats were provided with foods in different combinations (1 wet + 3 dry; 1 dry + 3 wet; 3 wet + 3 dry) in three separate experiments. Within each experiment cats were offered the wet and dry food combinations in two (naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…Similarly, the preferred single diet was a diet in which protein, fat and carbohydrate contributed 53%, 36% and 11% to metabolizable energy intake. These percentages closely match previously reported intake targets of 52% of ME as protein, 36% as fat and 12% as carbohydrate (Hewson‐Hughes et al, and Hewson‐Hughes et al., ) and vary from targets reported in another study based on literature data (Plantinga et al., ) only because the food compositions in Plantinga study precluded the possibility of 2% of ME intake as carbohydrate. Our results support the contention that this macronutrient composition approaches the ideal food chosen by cats.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the preferred single diet was a diet in which protein, fat and carbohydrate contributed 53%, 36% and 11% to metabolizable energy intake. These percentages closely match previously reported intake targets of 52% of ME as protein, 36% as fat and 12% as carbohydrate (Hewson‐Hughes et al, and Hewson‐Hughes et al., ) and vary from targets reported in another study based on literature data (Plantinga et al., ) only because the food compositions in Plantinga study precluded the possibility of 2% of ME intake as carbohydrate. Our results support the contention that this macronutrient composition approaches the ideal food chosen by cats.…”
Section: Discussionsupporting
confidence: 89%
“…Based on this assessment, it has been assumed that cats avoid carbohydrate‐rich diets and prefer food with high protein content. The geometric multivariate analysis concept allows the study of the interactions between protein, fat and carbohydrate on animals’ food preference (Hewson‐Hughes et al., , , ). Hewson‐Hughes et al () have demonstrated that cats are able to regulate their food intake to reach a target diet with a macronutrient energy composition of 52% protein, 36% fat and 12% carbohydrate.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated diet was 69.5% water with daily energy intake from protein 52%, from fat 46%, and from NFE only 2%, supporting the fact that cats are truly obligate carnivores. In a pair of studies Hewson-Hughes et al [20, 21] have indicated that providing wet food as well as dry may be beneficial to cat well-being. They demonstrated that cats will regulate their macronutrient intake to reach a “target” intake of total energy comprised of 52% protein, 36% fat, and 12% carbohydrate [20].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that cats will regulate their macronutrient intake to reach a “target” intake of total energy comprised of 52% protein, 36% fat, and 12% carbohydrate [20]. Importantly, this “target” could only be met by provision of wet foods in addition to dry and the cats consistently consumed more wet food (85% of total food intake) than dry when offered both [21]. More research is needed to determine if the shift from an obligatory meat-based natural diet to a meat-based and grain-based pet food rich in carbohydrates places the cat's metabolism under stress and possibly has unwanted negative health effects in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…That single diet will contain a fixed ratio of macronutrients (protein, fat and carbohydrate) and an individual fed that single diet may choose to eat more or less but cannot vary the ratio of dietary nutrient intake. In addition, an individual restricted to one diet may choose to sacrifice an important nutrient target to avoid over or under intake of another nutrient (Hewson-Hughes et al, 2013;Raubenheimer and Simpson, 1993;Raubenheimer, 1993, 2012). Conversely, when an individual has access to two or more food choices with different nutrient profiles, it may vary feed intake of the individual foods in such a way as to reach the intake target for one or more nutrients, as long as the nutrient targets can be attained through combinations of the available diets Simpson and Raubenheimer, 1993.…”
Section: Introductionmentioning
confidence: 98%